2013
DOI: 10.1177/1753193413506656
|View full text |Cite
|
Sign up to set email alerts
|

Nodular fasciitis of the hand: excision preserving ‘vital’ structures

Abstract: Nodular fasciitis is an extremely rare benign fibrous tumour of the hand. Although benign, the tumour is frequently adherent to tendons/nerves and joints of the hand. However, the tumour may spontaneously regress and does not tend to recur following excision with histologically positive margins. For the last 20 years, the author has adopted a specific management approach for these and other benign fibrous tumours of the hand. Following the clinical/radiological diagnosis, tumour excision is done preserving 'vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Al-Qattan and Arafah reported four cases of NF of the hand treated surgically over a 20-year period. They preserved vital structures such digital nerve, both digital arteries of a finger, the volar plate, and the flexor profundus tendon; none of these tumors had joint involvement [6].…”
Section: Discussionmentioning
confidence: 99%
“…Al-Qattan and Arafah reported four cases of NF of the hand treated surgically over a 20-year period. They preserved vital structures such digital nerve, both digital arteries of a finger, the volar plate, and the flexor profundus tendon; none of these tumors had joint involvement [6].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the malignant potential of nodular fasciitis and its oncogenic mechanism is currently being intensively investigated (4). In contrast, some nodular fasciitis lesions are self-limiting and spontaneously regress (7,8). Guo et al reported a case of 'malignant nodular fasciitis', which recurred several times and even metastasized to soft tissues (4).…”
Section: Discussionmentioning
confidence: 99%
“…Only 18 cases have been reported in the English literature. 3,6,[9][10][11][12][13][14][15][16][17][18][19] A third of these patients (n=6, 33%) suffered from pain or tenderness. In NF involving the palm, such symptoms appear to be less frequent than in other locations.…”
Section: Discussionmentioning
confidence: 99%